Research on the Performance of ZnO/Mg0.2Zn0.8O Flexible Ultraviolet Photodetector. Issue 1 (May 2021) - Wang, Meijiao; Jiang, Dayong; Li, Haoda; Weng, Siyuan; Sun, Jiamei; Duan, Yuhan; Zhang, Xiaolan; Zhao, Hongping
Abstract: The ZnO/Mg0.2 Zn0.8 O/Au flexible ultraviolet photodetector (UV PD) with a polyethylene terephthalate (PET) substrate was successfully prepared at room temperature, which is compared with Mg0.2 Zn0.8 O/Au without a ZnO buffer layer. ZnO/Mg0.2 Zn0.8 O/Au double-layer film is biased at low operating voltage, the spectral responsivity is improved by 2.77 times. This result provides a way to grow a buffer layer on PET to improve the responsieness of the device. After 0/50/100/200 bending times and storage for more than 90 days, the pet substrate maintains excellent mechanical stability and repeatability, which is suitable for practical applications.